Pengaruh Sistem Informasi Akuntansi Manajemen Terhadap Kinerja Manajerial Pengusaha Online di Kota Bogor - Roni Adi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to see the extent of the application of management accounting information systems by online entrepreneurs in the city of Bogor in encouraging the creation of good managerial performance. In general, onlone entrepreneurs in the city of Bogor who have used the concept of management financial information systems, on average, are ready to face global competition in this disruptive era. They realise that challenges and competition occur not only among fellow online entrepreneurs, but will also continue to compete with conventional entrepreneurs. So with the core they are fully aware of the managerial performance that they must develop and improve every time. The research used descriptive qualitative methods, data extraction was carried out by literacy studies and direct examination in the field on online entrepreneurs in Bogor City.